The selected writings of Christine de Pizan : new translations, criticism - Christine, de Pisan, approximately 1364-approximately 1431.; Blumenfeld-Kosinski, Renate, 1952- (New York : W.W. Norton & Co., 1997)
Contains selections from eighteen major works by Christine de Pizan, Europe's first professional woman writer, presented in contemporary translation with annotations, and includes an introduction, and seven critical analyses.
The selected writings of Christine de Pizan: From One hundred ballads and other ballads -- The God of love's letter -- From The letter to Othea -- From The debate on the romance of the rose -- From The tale of the shepherdess -- From The path of long study -- From The book of fortune's transformation -- A letter to Eustache Morel (February 10, 1404) -- Morel's answer -- From The book of the deeds and good conduct of the wise / King Charles V -- From The book of the city of ladies -- From the book of the three virtues -- From Christine's vision -- From the book of the body politic -- From One hundred ballads of a lover and a lady -- The lamentation on the evils that have befallen France -- From The book of peace -- From The letter on the prison of human life -- The Tale of Joan of Arc -- Criticsm: The stranger / Jacqueline Cerquiglini -- The problem of feminism in the fifteenth century / Beatrice Gottlieb -- Christien de Pizan and the misogynistic tradition / Renate Blumenfeld-Kosinski -- "Mothers to think back through": Who are they? The ambiguous example of Christine de Pizan / Sheila Delany -- Establishing authority: Boccaccio's De claris mulieribus and Christine de Pizan's Le livre de la cite des dames / Partricia A. Phillippy -- "Vox poetica, vox politica": the poet's entry into the political arena in the fifteenth century / Joel Blanchard -- Structures of authority in Christine de Pizan's Ditie de Jehanne d'Arc / Kevin Brownlee.
Includes bibliographical references (pages 391-392).
Translated from the old French.
Keywords: Christine, -- de Pisan, -- approximately 1364-approximately 1431. -- Translations into English; Christine, -- de Pisan, -- approximately 1364-approximately 1431 -- Criticism and interpretation; Christine, -- de Pisan, -- approximately 1364-approximately 1431 -- Translations into English; Christine, -- de Pisan, -- approximately 1364-approximately 1431.; Christine, -- Translations into English; Christine, -- Criticism and interpretation; Criticism, interpretation, etc; Translations